Tingkat pertumbuhan dan analisa protein sel-sel fibroblas fetal tikus hasil kultur in vitro - I.Djuwita .; Harlystiarini .; T. Widyaputri .; A. Efendi .; E.M Kaiin .; Nurhidayat . (Hemera Zoa, 2010)
Research has been conducted on in vitro growth of rat fetal fibroblast cells in Dulbecco S Modzfied Eagle Medium (DMEM) containing 10% Fetal Bovine Serum (FBS) and 50 µg/ml gentamycin. Culture was done in 5% CO2 incubator at 37°C for 10 days. Evaluation was done on the proliferation rate and the protein production after several passages. The growth of the fibroblast was confirmed by their morphology. The proliferation rate was done based on the population doubling time (PDT) by counting the number of cells in each passage by using Improved Neubauer hemocytometer. Protein secreted into the culture medium without FBS, designed as conditioned medium of rat fetal fibroblast (CM-RFF) was analysized using sodium dodecyl sulfatepolyacrilamidegel electrophoresis (SDS-PAGE) and biological assay on its potency to inhibit differentiation of bone marrow mesenchymal stem cells (BMSCs). Quantitative data were analyzed using statistical T-test on Minitab program. The results showed that based on the population doubling time, the proliferation rate was increased in line with the number of passages and basedon the SDP-PAGE analysis, the fibroblast cells secreted several protein included in estimation a 34 kDa protein that can be maintained until 9 passages. Addition of 25% CM-RFF into mDMEM (without FBS) did not increase the percentage of bone marrow mesenchymal stem cells-like, but signiJicantly increased the percentage of fibroblast. The presenced of LIF in the medium significantly increased the percentage of BMSCs-like and fibroblast. It can be concluded that thegrowth and protein secretion of rat fetal fibroblast cells can be maintain until 9 passages; but the secreted protein could not increased the percentage of the bone marrow mesenchymal stem cells like.